Duality of Interactions Between TGF-β and TNF-α During Tumor Formation - Liu, Zhi-wei; Zhang, Yi-ming; Zhang, Li-ying; Zhou, Ting; Li, Yang-yang; Zhou, Gu-cheng; Miao, Zhi-ming; Shang, Ming; He, Jin-peng; Ding, Nan-; Liu, Yong-qi (Frontiers in Immunology, 2022)
The tumor microenvironment is essential for the formation and development of tumors. Cytokines in the microenvironment may affect the growth, metastasis and prognosis of tumors, and play different roles in different stages of tumors, of which transforming growth factor β (TGF-β) and tumor necrosis factor α (TNF-α) are critical. The two have synergistic and antagonistic effect on tumor regulation. The inhibition of TGF-β can promote the formation rate of tumor, while TGF-β can promote the malignancy of tumor. TNF-α was initially determined to be a natural immune serum mediator that can induce tumor hemorrhagic necrosis, it has a wide range of biological activities and can be used clinically as a target to immune diseases as well as tumors. However, there are few reports on the interaction between the two in the tumor microenvironment. This paper combs the biological effect of the two in different aspects of different tumors. We summarized the changes and clinical medication rules of the two in different tissue cells, hoping to provide a new idea for the clinical application of the two cytokines.